Expression of an endoglucanase from Tribolium castaneum (TcEG1) in Saccharomyces cerevisiae. (9th December 2013) - Shirley, Derek; Oppert, Cris; Reynolds, Todd B.; Miracle, Bethany; Oppert, Brenda; Klingeman, William E.; Jurat‐Fuentes, Juan Luis
Abstract Insects are a largely unexploited resource in prospecting for novel cellulolytic enzymes to improve the production of ethanol fuel from lignocellulosic biomass. The cost of lignocellulosic ethanol production is expected to decrease by the combination of cellulose degradation (saccharification) and fermentation of the resulting glucose to ethanol in a single process, catalyzed by the yeast Saccharomyces cerevisiae transformed to express efficient cellulases. While S. cerevisiae is an established heterologous expression system, there are no available data on the functional expression of insect cellulolytic enzymes for this species. To address this knowledge gap, S. cerevisiae was transformed to express the full‐length cDNA encoding an endoglucanase from the red flour beetle, Tribolium castaneum (TcEG1), and evaluated the activity of the transgenic product (rTcEG1). Expression of the TcEG1 cDNA in S. cerevisiae was under control of the strong glyceraldehyde‐3 phosphate dehydrogenase promoter. Cultured transformed yeast secreted rTcEG1 protein as a functional β‐1, 4‐endoglucanase, which allowed transformants to survive on selective media containing cellulose as the only available carbon source. Evaluation of substrate specificity for secreted rTcEG1 demonstrated endoglucanase activity, although some activity was also detected against complex cellulose substrates. Potentially relevant to uses in biofuel production rTcEG1 activity increased with pH conditions, with the highest activity detected at pH 12. Our results demonstrate the potential for functional production of an insect cellulase in S. cerevisiae and confirm the stability of rTcEG1 activity in strong alkaline environments.